Open and Laparoscopic Colposuspension in Girls with Refractory Urinary Incontinence - Dobrowolska-Glazar, Barbara Anna; Groen, Luitzen A.; Nieuwhof-Leppink, Anka J.; Klijn, Aart J.; de Jong, Tom P. V. M.; Chrzan, Rafal (Frontiers in Pediatrics, 2017)
Introduction: Lower urinary tract symptoms (LUTS) are very common in children. Standard treatments consist of urotherapy, antibiotic prophylaxis, anti-muscarinics, physical therapy, and the treatment of coexisting constipation. A small group of girls also present with stress incontinence or with stress-induced urge incontinence. In cases of persistent LUTS due to congenital bladder neck insufficiency (BNI), surgical treatment might be considered. The aim of this paper is to assess the results of open and laparoscopic colposuspension in children with refractory urinary incontinence (UI). Materials and methods: The results of 18 open and 18 laparoscopic consecutive colposuspensions were analyzed. All patients had urinary incontinence (UI) and failed conservative treatment. BNI was proven by repeated perineal ultrasound and video-urodynamic study. The laparoscopic procedure was performed preperitoneally and the open procedure was via a transverse lower abdominal incision. The same postoperative protocol was used in both groups. Results: The mean operation time was 65 min for the open and 90 min for the lap procedure (p<0.05). Full success was achieved in 7/18 in the open and in 8/18 in the lap group and partial response was seen in 3/18 and in 5/18, respectively (p=0.64). No intraoperative complications occurred in this cohort. Conclusions: Open and laparoscopic colposuspension can be used to treat refractory UI in children with bladder neck insufficiency when non-invasive methods fail.